Model comparison for initial density fluctuations in high-energy heavy-ion collisions - Flörchinger, Stefan; Grossi, Eduardo; Vahid Yousefnia, Kianusch (Physical review, 2020)
Four models for the initial conditions of a fluid dynamic description of high-energy heavy-ion collisions are analyzed and compared. We study expectation values and event-by-event fluctuations in the initial transverse energy density profiles from Pb-Pb collisions. Specifically, introducing a Fourier-Bessel mode expansion for fluctuations, we determine expectation values and two-mode correlation functions of the expansion coefficients. The analytically solvable independent point-sources model is compared to an initial-state model based on Glauber theory and two models based on the color glass condensate framework. We find that the large-wavelength modes of all investigated models show universal properties for central collisions and also discuss to what extent general properties of initial conditions can be understood analytically.
Gesehen am 11.01.2021